DEVELOPMENT STRATEGY OF KNOWLEDGE AND AVAILABILITY OF LOCAL LEVEL OF EAST NUSA TENGGARA IN THE MIDDLE OF CLIMATE CHANGE THROUGH EDUCATION IN KUPANG VOCATIONAL PUBLIC SCHOOL - Trigutomo, Wahyu Hadi (Universitas Pendidikan Indonesia, 2017)
Nowadays, the availability of national food cannot accommodate all the food needs of nation’s people, especially in each region. This current issue is caused by the absence of an effective arrangement, the absence of synchronization among state institutions, especially among the agricultural, trade and housing agencies, and the presence of an extreme climate change currently. In addition, the issues of the regeneration of farmers that have not shown any continuity that had been cut off among the younger generations led to the changes in the pattern of community life in the region. Therefore, based on the aforesaid issues, this paper aims at finding out on how the strategy and policy of food development in the local food availability in the midst of climate change today can be overcome by changing the mindset of consumptive to productive young generation through agricultural education, utilization of empty land which is available for planting food crops, empowerment of farmer groups, socialization of the local food potentials in East Nusa Tenggara. As a result, the food security can be realized and the region cannot be dependent its food needs on the other regions. Therefore, the writer attempts to formulate the strategy of food security developments from education aspects through the Dick Carey development strategy. Food is an important and strategic commodity for the region because food is the basic human need that must be provided collectively by the government and society as mandated by the Acts No. 7 of 1996 on food. With respect to the Acts No. 7 of 1996 on food, it is stated that the Government organizes the regulation, guidance, control and supervision of the community, and organizes the process of production and supply, trade, distribution and in the same time, the Government also serves as a consumer that is entitled to adequate food, in terms of quantity and quality, safety, nutrition, variety, equity, and affordability by all society. The availability of national food can be fully fulfilled if it is commenced from the food sufficiency in the levels of family. In regard to the local area, it is marked by the existence of food consumption which can fulfill the sufficiency of every individual, in terms of balanced nutrition. In fact, it then has an impact on sufficiency of food and the nutrition status of Indonesian society can be fulfilled locally, especially in East Nusa Tenggara. The availability of food in terms of adequate quantities and types for the whole community locally in East Nusa Tenggara, smooth food distribution, cheap food prices and affordability by the all levels of society locally in East Nusa Tenggara, evenly distributed to all families in the region.